Significados Atribuidos A La Aceptación De La Orientación Sexual, Caracteristicas De La Relación Parental Y De Pareja En Un Grupo De Adolescentes Homosexuales (2019)
This investigation pretended to describe what are the attributed meanings to the acceptance of sexual orientation, characteristics of the parental and partner relationships in a group of homosexual adolescents. The methodology implemented was qualitative with narrative design. The participants corresponded of six adolescents, three men and three women, the interview was carried out with every single one and recorded in audio tapes; from that an inductive categorial analysis was carried out and categories were established. In the findings highlights a series of difficulties occurred with regard to the acceptance process, in which family is also affected, by stereotypes, prejudice and tabus with regards to homosexual people.